The preoperative alkaline phosphatase-to-platelet ratio index is an independent prognostic factor for hepatocellular carcinoma after hepatic resection. Issue 51 (December 2016) - Yu, Ya-Qun; Li, Jun; Liao, Yan; Chen, Qian; Liao, Wei-Jia; Huang, Jian
Abstract : Abstract: A simple, inexpensive, and readily available prognostic index is highly needed to accurately predict the prognosis of hepatocellular carcinoma (HCC). This study aimed to develop a simple prognostic index using routine laboratory tests, alkaline phosphatase-to-platelet count ratio index (APPRI), to predict the likelihood of postoperative survival in HCC patients. A total of 246 patients with HCC undergoing curative resection were retrospectively analyzed. Cutoff point for APPRI was calculated using receiver operating characteristic curve analysis, and then the patients were divided into the low-APPRI group (APPRI ⩽ 4.0) and the high-APPRI group (APPRI > 4.0). The influences of APPRI on disease-free survival (DFS) and overall survival (OS) were tested by the Kaplan–Meier method, and multivariate analysis using Cox regression. Elevated APPRI was associated with age, cirrhosis, and aspartate aminotransferase (AST) in HCC. Univariate analysis showed that APPRI > 4.0, tumor size >6 cm, multiple tumors, Barcelona-clinic liver cancer stages B to C, and AST > 40 U/L were significant predictors of worse DFS and OS. A multivariate analysis suggested that APPRI > 4.0 was an independent factor for DFS (hazard ratio [HR] = 1.689; 95% confidence interval [CI], 1.139–2.505; P = 0.009) and OS (HR = 1.664; 95% CI, 1.123–2.466; P = 0.011). Preoperative APPRI > 4.0 was a powerful prognostic predictor of adverse DFS and OS in HCC after surgery. The APPRI may be a promising prognostic marker for HCC after surgical resection.